Price shocks, news disclosures, and asymmetric drifts - LU, Hai (Institutional Knowledge at Singapore Management University, 2013)
Motivated by investor disagreement and corporate disclosure literatures, we examinehow stock price shocks aﬀect future stock returns. We ﬁnd that both large short-termprice drops and hikes are followed by negative abnormal returns over the subsequent year,consistent with the conjecture that price shocks are useful indicators of inter-temporalspikes in investor disagreement and investor opinion converges gradually. The asymmetricdrifts, return continuation for negative price shocks versus return reversal for positive ones,are in sharp contrast to the general ﬁndings of symmetric drifts in corporate event studies.Moreover, price shocks associated with public news events are followed by signiﬁcantlyweaker downward drifts, suggesting that news disclosures mitigate disagreement-inducedoverpricing. Examining the dynamics of a disagreement proxy during and after price shocks,we provide further evidence for the disagreement hypothesis. The economic signiﬁcance ofthe price shock eﬀect is illustrated with a revised momentum strategy that generates anannualized abnormal return of 16.92 percent.